Multiscale Vascular Enhancement Filter Applied to In Vivo Morphologic and Functional Photoacoustic Imaging of Rat Ocular Vasculature - Huangxuan Zhao; Ke Li; Ningbo Chen; Kunya Zhang; Lidai Wang; Riqiang Lin; Xiaojing Gong; Liang Song; Zhicheng Liu; Chengbo Liu (IEEE Photonics Journal, 2019)
Optical-resolution photoacoustic microscopy (OR-PAM) is used for in vivo imaging of a variety of albino and pigmented eyes taking advantages of requiring no exogenous dye, performing high-resolution imaging, and achieving morphologic and functional imaging at the same time. However, to accurately diagnose the ophthalmic disease in the OR-PAM images, vascular enhancement algorithms are necessary for extracting vessels and quantifying them correctly. Vascular enhancement algorithms developed for other imaging technologies, are not suitable to be used for OR-PAM, because of the underlying differences in the physics of the formation of images. In this study, a new vascular enhancement algorithm called photoacoustic imaging vasculature enhancement filter (PAIVEF) is proposed, which not only enhances vasculature including micro-vessels signals, suppresses noise signals effectively, but also achieves highly sensitive and accurate enhancement of the vasculature within a large depth range in and out of the system's depth of focus (DOF). Using the PAIVEF, the morphologic and functional 3D images of the whole rat's ocular anterior vasculature segment was displayed simultaneously for a depth range of ∼0.6 mm, which was ∼7 times of the system's DOF. This study paves the way for the application of OR-PAM technology in ophthalmic disease research.